2000
DOI: 10.1128/aem.66.7.2996-3003.2000
|View full text |Cite
|
Sign up to set email alerts
|

A New Method To Monitor Airborne Inoculum of the Fungal Plant Pathogens Mycosphaerella brassicicola and Botrytis cinerea

Abstract: We describe a new microtiter immunospore trapping device (MTIST device) that uses a suction system to directly trap air particulates by impaction in microtiter wells. This device can be used for rapid detection and immunoquantification of ascospores of Mycosphaerella brassicicola and conidia of Botrytis cinerea by an enzymelinked immunosorbent assay (ELISA) under controlled environmental conditions. For ascospores of M. brassicicola correlation coefficients (r 2 ) of 0.943 and 0.9514 were observed for the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 20 publications
1
53
0
1
Order By: Relevance
“…These include immunological and DNA and polymerase chain reaction (PCR)-based methods. Immunological detection of Mycosphaerella brassicicola from spore traps has been developed to rationalize pesticide applications within crop protection programs (42). However, pathogen discrimination is still dependent on spore production, which may occur at a late stage in development in the disease cycle and by which stage prophylactic intervention may not be a management option.…”
mentioning
confidence: 99%
“…These include immunological and DNA and polymerase chain reaction (PCR)-based methods. Immunological detection of Mycosphaerella brassicicola from spore traps has been developed to rationalize pesticide applications within crop protection programs (42). However, pathogen discrimination is still dependent on spore production, which may occur at a late stage in development in the disease cycle and by which stage prophylactic intervention may not be a management option.…”
mentioning
confidence: 99%
“…The trap was tested in wind tunnel experiments with Alternaria brassicae conidia utilizing a monoclonal antibody against germinating conidia of this pathogen (36,37). More recently, a new particle-trapping device, the microtiter immunospore trap, was developed by the Burkard Manufacturing Co., Rickmansworth, UK (19). The device uses a suction system to collect airborne particles directly into the wells of a microtiter plate.…”
Section: Discussionmentioning
confidence: 99%
“…The device uses a suction system to collect airborne particles directly into the wells of a microtiter plate. Kennedy et al (19) demonstrated the utility of this device for detecting airborne spores of M. brassicicola and B. cinerea by ELISA. We found in this study that P. pachyrhizi urediniospores captured in a passive air sampler could be quickly and easily identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques have been successfully applied to detect bacteria and fungi in air samples (Schmechel et al 2003;Speight et al 1997;Nugent 1997;Kennedy et al 2000). Given the nature of these detection techniques, liquid and filter material are preferable sampling media.…”
Section: Introductionmentioning
confidence: 99%